Pengembangan Video Animasi Fabel dalam Menanamkan Nilai-Nilai Moral Anak Kelompok A RA UMDI Ujung Baru - Balgis, Balgis; Asmara Palintan, Tien; Ashari, Novita; Tadzkirah, Tadzkirah (UIN Fatmawati Sukarno Bengkulu, 2025)
This study aims to describe the understanding of moral values in Group A children at RA UMDI Ujung Baru, develop animated fable video media, and test its effectiveness in instilling moral values. The study used the Research and Development (R&D) method with the Borg & Gall model, involving eight children (five boys and three girls). The results showed that the lack of varied learning media was a barrier to engaging children's interest in moral material. Teachers tended to use lecture or storytelling methods without the support of interactive media. The development process continued to the limited product revision stage. Validation by media experts reached 91.6% and material experts 85.4%, both in the very appropriate category. Product trials showed a teacher response of 83.3% (very good), teacher observations 78% (good), and children observations 91.3% (very appropriate).